Image segmentation algorithms on female pelvic ultrasound images - Patrícia F. Silva (2011)
The processing and analysis of structures presented in images has been one of the areas of Computational Vision with greater potential and applicability. The main goal of the researchers of this area has been the development of new computational methodologies to study the behaviour of structures in images. The mentioned image-based analysis is very important in many domains. For example, in Medicine, the information obtained by the proposed automatic analysis is crucial to understand the functioning and the behaviour of organs, and thus to assist medical doctors. A faithful simulation of organs is extremely important to improve the accuracy of medical virtual systems, as of the human body and of computational surgical simulators and robotic surgery. In this work, several algorithms of image segmentation are evaluated on ultrasound images acquired from female pelvic cavity.